How Social Structure Drives the Population Dynamics of the Common Vampire Bat (Desmodus rotundus, Phyllostomidae). (8th December 2017) - Huguin, Maïlis; Arechiga-Ceballos, Nidia; Delaval, Marguerite; Guidez, Amandine; de Castro, Isaï Jorge; Lacoste, Vincent; Salmier, Arielle; Setién, Alvaro Aguilar; Silva, Claudia Regina; Lavergne, Anne; de Thoisy, Benoit
Abstract: Social systems are major drivers of population structure and gene flow, with important effects on dynamics and dispersal of associated populations of parasites. Among bats, the common vampire bat ( Desmodus rotundus ) has likely one of the most complex social structures. Using autosomal and mitochondrial markers on vampires from Mexico, French Guiana, and North Brazil, from both roosting and foraging areas, we observed an isolation by distance at the wider scale and lower but significant differentiation between closer populations (<50 km). All populations had a low level of relatedness and showed deviations from Hardy–Weinberg equilibrium and a low but significant inbreeding coefficient. The associated heterozygote deficiency was likely related to a Wahlund effect and to cryptic structures, reflecting social groups living in syntopy, both in roosting and foraging areas, with only limited admixture. Discrepancy between mitochondrial and nuclear markers suggests female philopatry and higher dispersal rates in males, associated with peripheral positions in the groups. Vampires are also the main neotropical reservoir for rabies virus, one of the main lethal pathogens for humans. Female social behaviors and trophallaxis may favor a rapid spread of virus to related and unrelated offspring and females. The high dispersal capacity of males may explain the wider circulation of viruses and the inefficacy of bat population controls. In such opportunistic species, gene connectivity should be considered for management decision making. Strategies such as culling could induce immigration of bats from neighboring colonies to fill vacant roosts and feeding areas, associated with the dispersal of viral strains.